Perspectives in Ecological Theory - Levin, Simon A.; May, Robert M. (Robert McCredie), 1936-; Roughgarden, Joan (Book collections on Project MUSE., 1989)
This volume presents an overview of current accomplishments and future directions in ecological theory. The twenty-three chapters cover a broad range of important topics, from the physiology and behavior of individuals or groups of organisms, through population dynamics and community structure, to the ecology of ecosystems and the geochemical cycles of the entire biosphere. The authors focus on ways in which theory, whether expressed mathematically or verbally, can contribute to defining and solving fundamental problems in ecology. A second aim is to highlight areas where dialogue between theorists and empiricists is likely to be especially rewarding.